Simulation on Concrete Structure Demolition using Explosive Method - mmed Alias Yusof, Moha; Mohamad Nor, Norazman; Ismail, Ariffin; Azani Yahya, Muhammad; Munikanan, Vikneswaran (International Journal of Engineering and Technology, 2018)
Demolition of any structure is the process of destroying down or collapsing down of large buildings after its useful life period with the help of some equipment. There are several method used in demolition building structure applied around the world nowadays such as using wrecked ball, powered plant or demolition machines, hydro demolition, saw cut and explosive. The choice of choosing a demolition method depends on a number of factors such as the project conditions, site constraints, and sensitivity of the neighborhood and availability of equipment environment. However demolition work is one of the most dangerous operations in construction. One of the common reasons is easy to cause injury to human workers due to the difficulty of accessing into or working inside a building which is under demolition. Demolition using explosive is effective method to use compare too mechanically if we look down from degree of time. It is because the explosive charges used to tearing down a structure can shorten the time. Just in one blow the building structure is tearing down completely.Â The objective of this research is to simulate the demolition of five storey reinforced concrete structure frame using AUTODYN simulation software. A total 200 grams of TNT charge is placed at three different location of the structure column, which is at the bottom, middle and upper section of the column to study the effect of the explosive on the column. From the simulation results, it shows that location of the explosive on the upper point of the column damaged badly the structure as compare with the other location.Â Â